2021
DOI: 10.3389/fpubh.2021.683291
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrics of Persian Version of the Ageism Survey Among an Iranian Older Adult Population During COVID-19 Pandemic

Abstract: Background: Studies have revealed an increase in discrimination, neglect, and abuse among the older adult population during this period. This study assessed the validity and reliability of the Persian version of the ageism survey instrument tested on a sample of the Iranian older adult population during coronavirus disease (COVID-19) pandemic. An important move in counteracting ageism is to classify the ageism scale comprehensively by employing adequate psychometrics.Methods: The Persian version of the ageism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…Among the goodness of Fit, the most common ones were evaluated for the presented model. From the absolute fit index, Chi-square (CMIN), root mean square error of approximation (RMSEA < 0.05), and among the Comparative fit indices, Tucker-Lewis Index (TLI > 0.9), Incremental Fit Index (IFI > 0.9), Comparative Fit Index (CFI > 0.9), and among the parsimonious fit indices, Parsimonious Normed Fit Index (PNFI > 0.5) and Parsimonious Comparative Fit Index (PCFI > 0.5) were calculated, and finally, the ratio of chi-square to degrees of freedom (CMIN/DF < 3) was also evaluated [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the goodness of Fit, the most common ones were evaluated for the presented model. From the absolute fit index, Chi-square (CMIN), root mean square error of approximation (RMSEA < 0.05), and among the Comparative fit indices, Tucker-Lewis Index (TLI > 0.9), Incremental Fit Index (IFI > 0.9), Comparative Fit Index (CFI > 0.9), and among the parsimonious fit indices, Parsimonious Normed Fit Index (PNFI > 0.5) and Parsimonious Comparative Fit Index (PCFI > 0.5) were calculated, and finally, the ratio of chi-square to degrees of freedom (CMIN/DF < 3) was also evaluated [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The same results were found by Ayalon and Cohn‐Schwartz (2021), who through a telephone survey of older adults in Israel showed that both self‐defined ageing and health‐related worries significantly predicted COVID‐19‐related concerns. In another relevant paper, Nia et al's (2021) survey proved that an increase in ageism and age‐related discriminatory attitudes resulted from the pandemic in Iran.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Human beings are constantly growing and moving from one stage to the other. This personal development process is an unpredictable and demanding process during each of the development stages during stressful circumstances ( Maddi, 2004 ; Sharif Nia et al, 2021 ). These stress conditions can have a negative effect on performance, motivation, and health if they are not handled well ( Bonanno, 2004 ).…”
Section: Introductionmentioning
confidence: 99%